Frequency of various cardiac complications in children with repaired tetralogy of Fallot identified by computer tomography - Azhar M. Kabdullina; Valentin E. Sinitsyn; Raushan I. Rakhimzhanova; Tairkhan B. Dautov; Aigul B. Saduakassova; Baurzhan B. Kaliyev; Lyazzat A. Bastarbekova; Zhanar A. Moldakhanova (Digital Diagnostics, 2023)
BACKGROUND: Tetralogy of Fallot represents 7–10% of all cases of congenital heart disease, as it occurs in approximately 0.5 per 1,000 live births and is the second most common form of complex congenital heart disease. Advances in diagnosis, surgical techniques, and postoperative treatment have led to an increasing number of patients reaching adulthood, with a dramatic increase in the survival rate to almost 90% at 30 years, thereby creating a need for long-term monitoring of certain anatomic parameters to identify complications in a timely manner. This study aimed to investigate the frequency of computed tomography detected complications after radical correction of Tetralogy of Fallot in pediatric patients.